Validity And Reliability Of Indonesian Social Media Disorder (SMD) Scale In Adolescent - Suzy Yusna Dewi; Yunita Mansyah Lestari (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2020)
Social media is popular in various circles, especially adolescents. Adolescent are the most vulnerable to be affected by technology. The excessive use of social media will make it difficult for adolescents who are addicted to social media. This study aims to adapt and assess the validity and reliability of the Social Media Disorder (SMD) questionnaire in indonesian. The subjects of the study were adolescents aged 13-19 years and living in DKI Jakarta. Data were collected on 21 April - 27 April 2019 using the method of consecutive sampling and snowball sampling with a questionnaire via the Googleform link. The number of research respondents were 30 people, 40% male and 60% female. The data was processed using SPSS 25. The results observed with the value of Cronbach's Alpha = 0.802 and r = 0.481-0.887, which means the Indonesian SMD questionnaire have good validity and reliability.